An immense world : how animal senses reveal the hidden realms around us - Yong, Ed (London : The Bodley Head Ltd, 2022)
In'An Immense World', author and acclaimed science journalist Ed Yong coaxes us beyond the confines of our own senses, allowing us to perceive the skeins of scent, waves of electromagnetism, and pulses of pressure that surround us. Because in order to understand our world we don't need to travel to other places; we need to see through other eyes
Includes bibliographical references and index
Keywords: Animal behavior; Senses and sensation